Site of nitrogen accumulation in tulip (Tulipa gesneriana L.) roots during winter - Komiyama S. (2014)
It was found that tulip (Tulipa gesneriana L.) plants accumulate a large amount of nitrogen in their roots during the winter season, which is efficiently used for rapid shoot growth after sprouting in spring. In the present paper, the site and origin of nitrogen accumulation in tulip roots were investigated in a vertical split-root experiment. Tulip roots were separated into upper and lower half parts in a two-compartment tray, and the culture solution was separately supplied for a week. Culture solution with N-free medium or that containing 15N-labeled nitrate (2 mM 15NO3- + 0.5 mM NH4+) or 15N-labeled ammonium (2 mM NO3- + 0.5 mM 15NH4+) was supplied to individual trays to determine the metabolic fate of nitrate and ammonium nitrogen in either part of the roots. The results indicated that nitrate and ammonium absorption activities were similar between the lower and upper half-parts of the tulip roots. The absorbed 15N predominantly accumulated either in the upper or lower part of the roots in direct contact with 15N-labeled medium, and only a small portion of 15N was translocated to the other part. In the root part treated with 15N-labeled medium, most of the absorbed nitrogen was in ethanol soluble forms, and free glutamine and glutamic acid were intensely labeled with 15N. Also in the root parts directly in contact with nitrogen, the glutamine concentration in either the upper or the lower roots was considerably enhanced. On the other hand, nitrogen application did not affect the 4-methyleneglutamine concentration. Sucrose and glucose were the major soluble sugars in tulip roots, and the concentration was reduced at the nitrogen absorption site, possibly due to energy and carbon consumption for the absorption and assimilation of nitrogen.